The Pope's Public Reason: A Religious yet Public Case for Welcoming Refugees. Issue 1 (1st June 2021) - Bardon, Aurélia
Abstract: Since the beginning of Europe's "refugee crisis, " Pope Francis has repeatedly argued that we should welcome refugees. This, he said, is an obligation for Christians who have "a duty of justice, of civility, and of solidarity." This religious justification is a problem for liberal political philosophers who are committed to the idea of public reason: state action, they argue, must be justified to all citizens based on public, generally accessible reasons. In this article, I argue that the claim that liberal public reason fully excludes religion from the public sphere is misguided; not all religious reasons are incompatible with the demands of Rawlsian public reason. Understanding how a religious reason can be public requires looking into both what makes a reason religious and what makes a reason public. I show that the pope's reason supporting the claim that we should welcome refugees is both religious and public.